Taste Masking of Granulated Acetaminophen by Water Insoluble Ethylcellulose Coating - Amit Bansal; Brian Krieg; Navneet Sharma; James McGinnis; Inderdeep Bhatia; Carlos Paz (Folia Medica, 2021)
Introduction: Bitter tasting of drugs leads to non-compliance especially in the case of pediatric patients due to their inability to swal-low medication. Aim: In this study, we aimed to mask the bitter taste of acetaminophen (APAP) particles through coating. Materials and methods: A pH independent water insoluble ethylcellulose polymer was used to coat the APAP. The coating of water insoluble ethylcellulose on APAP can have a significant impact on the dissolution profile. Various grades of APAP were used for coating; fine grade, Compap L90% having wide particle size distribution (PSD), and a special granular (SG) APAP 1680 having narrow PSD. Coating was performed using top spray (Vector) for Compap L90% and SG APAP 1680 grade of APAP. Results: Bitter taste of SG APAP was masked after spraying dispersion equivalent to a weight gain of 10% compared to 35% used for Compap L90%. Using bottom spray (Wurster coater, GPCP 2.0), coating was performed on SG APAP 1680 grade of APAP by spraying aqueous dispersion of ethylcellulose (Surelease) equivalent to a weight gain of 10%. The scalability of the top spray process was also evaluated in GPCG 30 and bitter taste was masked by using Surelease dispersion equivalent to a weight gain of 6%. Coated APAP was examined for particle size (PS), particle size distribution (PSD), flowability, and drug release profile. Dissolution was performed using USP apparatus 2 and 4 in phosphate buffer and evaluated for mechanism of drug release. Particle size obtained for coated SG APAP 1680 via top and bottom spray process was 404 µm d(90) and 487 µm d(90) respectively. Conclusions: The results of the study demonstrated the potential of Surelease dispersion in taste masking. The use of SG APAP 1680 having narrow PSD allowed taste masking to achieve at low weight gain without greatly affecting the dissolution profile.